Strength properties of aerated cement composite reinforced with steel fibres. (2021) - Selvakumar, M.; Geetha, S.; Muthulakshmi, S.
Abstract: Aerated concrete is a type of lightweight concrete having densities ranging from 400–1800 kg/m 3 . Lightweight concrete is gaining importance as a construction material and it finds use as building blocks for constructing infilled walls in multistoried structures. The advantage of using these blocks is the reduced density and good thermal insulation properties due to the porous nature of the matrix. The disadvantage is that in commercial blocks the strength is very low which is less than 6 MPa. The objective of this study is to optimise the mix proportion of aerated concrete with improved strength and durability properties so that it can be used in precast structural elements like wall panels. The studies resulted in a light weight concrete that had density of 1265 kg/m 3, a compressive strength of 19.93 MPa and a flexural strength of 3.86 MPa. Sorptivity tests were also done to test the durability parameters which depend on the pore distribution. Response surface methodology was adopted in this study to find the significant factors that influence each parameter. Finally optimization was done considering the criteria for high strength and low density and sorptivity.